Validation study associating glutaminase promoter variations with hepatic encephalopathy in East Asian populations. Issue 4 (April 2017) - Ahn, Jem Ma; Kim, Chang Ha; Um, Soon Ho; Kim, Kyung Mee; Kim, Tae Hyung; Yim, Sun Young; Choi, Hyuk Soon; Kim, Eun Sun; Keum, Bora; Seo, Yeon Seok; Yim, Hyung Joon; Jeen, Yoon Tae; et al.
Abstract: Background and Aim: In a recent study, microsatellite variations (GCA tandem repeats) in the promoter region of the (kidney‐type) glutaminase gene were associated with the development of hepatic encephalopathy (HE) in Spanish patients with cirrhosis. The objective of this study was to validate the relation between microsatellite variations in the glutaminase promoter region and the development of overt HE in Korean patients with liver cirrhosis. Methods: We performed a prospective cohort study of 154 cirrhotic patients who underwent a glutaminase microsatellite study without previous overt HE history at baseline. The primary end point was the first episode of overt HE. The microsatellite length was categorized into three groups based on its repeated number, with a cutoff value of 14; 65 (42.2%), 70 (45.5%), and 19 (12.3%) patients had the short‐short, short‐long, and long‐long alleles, respectively. Results: Over a median 3.5 years of follow‐up (range = 0.1–4.4), overt HE developed in 28 patients (18.2%). The 3‐year cumulative incidence of overt HE was 18.4%. Multivariate Cox model indicated that past hepatocellular carcinoma history, alcoholic etiology for cirrhosis, higher Model for End‐Stage Liver Disease scores and their deterioration, and serum ammonium levels were independently associated with HE development. However, microsatellite length was not associated with the development of overt HE. Conclusions: In Korean patients with cirrhosis, microsatellite variations in the glutaminase promoter region were not associated with development of overt HE. Thus, additional studies are needed to identify other genetic factors related to glutaminase activity in Asians with overt HE.